Dilematika Nafkah Madiyah Anak Dalam Putusan Pengadilan Agama Tanjungkarang Nomor 0846/Pdt.G/2015/PA.Tnk - Lisnawati, Lisnawati (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Applications for māḍiyah maintenance or debt support, especially for children, are often rejected by the courts. This is based on the existence of jurisprudence based on the decision of the Supreme Court Number 608/K/AG/2003. One example is the decision of the Tanjungkarang Religious Court Number 0846/Pdt.G/2015/PA.Tnk. This research is normative legal research using a case approach. Sources of research data consist of primary, secondary, and tertiary legal materials. The data obtained were then analyzed using the content analysis method. Decision Number 0846/Pdt.G/2015/PA.Tnk. shows that the legal basis for refusing claims for māḍiyah maintenance for children in divorce is legal considerations as considered by the Supreme Court in its decision rejecting lawsuits for past maintenance for children, namely that the father's obligation to provide for his child is lil-intifāʻ, not lit-tamlīk, then a person's negligence fathers who do not provide for their children cannot be sued. This leads to injustice because māḍiyah maintenance is not granted to children. This will certainly be detrimental to the life and welfare of the child, who in other circumstances can become a shield for a father who neglects to provide for his child. Māḍiyah livelihood is a form of protection for the rights of divorced women and children born during the marriage. This is in line with the verses of the Koran and hadith which talk about the obligation of a father to his wife and children to provide maintenance. In addition, such provisions can also be found in child protection legal instruments in force in Indonesia. The law should pay more attention to the lives of children by issuing judges' decisions that are good for them so that it will close gaps for husbands or fathers who can be negligent in their obligations, and protect divorced women from a double burden.